INCREASING PERFORMANCE OF OIL PALM NPK FERTILIZATION WITH RISK MANAGEMENT AND ANALYTIC HIERARCHY PROCESS (AHP) - Rofiq Kurniawan; Agustinus Hariadi (ABNUS Publisher, 2022)
This research is intended to improve the performance of oil palm fertilization by examining the fertilizer procurement process. The research design that will be carried out in this study is based on the problems studied using descriptive analysis methods. Measurement of priority risk using FMEA and formulation of mitigation strategies using AHP (Analytic Hierarchy Process) by collecting data through observation, questionnaires with stakeholders who have expertise in their respective fields at the research site. One of the plantation crops that are widely cultivated by large plantation companies is oil palm. The moratorium on oil palm plantation permits for the addition of new land for 3 years encourages companies to increase crop productivity on existing plantation lands, one of which is fertilization. Constraints experienced in fertilizing on mature plants are the incompatibility of the fertilizer applied to the planned one. So that the increase in fertilization performance can be done through improvements in the procurement process. The purpose of this research is to study the risk priorities in the planning process to the acceptance of fertilizers in the procurement of fertilizers. The results showed that the priority risk of fertilizer procurement planning is that the budget availability is not in accordance with the recommendations (RPN 27), the supplier selection process is the announcement of the old tender (RPN 18), the dropping/delivery process is a late contract signed (RPN 18), the acceptance process is that the fertilizer is accepted. past the time period (RPN 18). The criteria are fertilizer procurement planning, supplier selection, fertilizer delivery and fertilizer receipts with successive values ​​of 0.575, 0.214, 0.134, 0.077. The alternatives are ensuring budget adequacy, adding fertilizer suppliers, improving communication between fertilizer providers and users, determining the timing of fertilizer application, increasing the frequency of fertilizer quality inspections and using information technology in fertilization. Improving the performance of fertilizer procurement can be done with three main strategies, namely improving the budgeting system, improving procurement documents, selecting suppliers with a multi-winner system.